2015
DOI: 10.18632/oncotarget.4113
|View full text |Cite
|
Sign up to set email alerts
|

A six gene expression signature defines aggressive subtypes and predicts outcome in childhood and adult acute lymphoblastic leukemia

Abstract: Abnormal gene expression in cancer represents an under-explored source of cancer markers and therapeutic targets. In order to identify gene expression signatures associated with survival in acute lymphoblastic leukemia (ALL), a strategy was designed to search for aberrant gene activity, which consists of applying several filters to transcriptomic datasets from two pediatric ALL studies. Six genes whose expression in leukemic blasts was associated with prognosis were identified:three genes predicting poor progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 30 publications
1
41
0
2
Order By: Relevance
“…It has recently been demonstrated that STARD4 expression could be used as poor prognosis gene in a six genes signature that defines aggressive subtypes in adult acute lymphoblastic leukemia [84]. …”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that STARD4 expression could be used as poor prognosis gene in a six genes signature that defines aggressive subtypes in adult acute lymphoblastic leukemia [84]. …”
Section: Discussionmentioning
confidence: 99%
“…lists of genes able to predict clinical outcome [41] or for molecular subtyping, i.e. list of genes able to classify different subtypes of a disease [42][43]. However, even if markers performed well, gene signatures derived from studies on the same treatments and diseases often resulted in gene lists with little overlap [44].…”
Section: Discussionmentioning
confidence: 99%
“…42 Oxidized low-density lipoprotein receptor-1 (OLR-1), is a type II transmembrane receptor of the C-type lectin family that induces oxidative stress, activates tumor necrosis factor a TNFa/nuclear factor-kB (NFkB), upregulates the expression of monocyte chemoattractant protein-1 (MCP1), a key mediator of inflammatory processes, and has a proinflammatory role in cardiovascular disease. [43][44][45] calcium/calmodulin-dependent protein kinase kinase 2 (CAMKK2) transcripts were downregulated in CMML CD14 1 monocytes. As previous studies have demonstrated, a crucial role of the CAMKK2-59-AMP-activated protein kinase catalytic subunit-1 (PRKAA1) axis in the differentiation of monocytes into macrophages, our data are consistent with the observation that the differentiation from monocytes to macrophages is compromised in CMML.…”
Section: Identification Of Gene Expression Differences Between Cmml Pmentioning
confidence: 99%